(untitled) (Eurasian Journal of Humanities and Social Sciences, 2023)
This article explores the intricate relationship between pedagogy and psychology within the realm of education. It delves into how pedagogical approaches and instructional strategies are informed by psychological principles to create effective and learner-centric teaching environments. The article highlights the importance of understanding diverse learning styles, addressing individual differences, and promoting positive learning outcomes through the synergy of pedagogy and psychology